Battery Capacity Estimation for Building Integrated Photovoltaic System: Design Study for Different Geographical Location(s). (December 2017) - Yassin, Mohammed A.M.; Kolhe, Mohan; Sharma, Arvind; Garud, Shirish
Abstract: Building Integrated Photovoltaic system (BIPV) with energy storage (ES) can help in reducing the peak demand, improving the power quality and control dispatching of the power. Adding a proper size of battery ES to the grid-connected PV system could reduce the overall investment cost as well as reducing the grid-dependency. A typical battery energy storage capacity is going to be determined by considering the real-time operational (PV production as well as load consumption) data. In this study, real-time operational data of a residential load (C6 house) with BIPV system located Southern Norway as well as institutional load (Teri university) with BIPV located in New Delhi, India are used for estimating the size of the battery energy storage considering the maximum reduction in the annual electricity bill. The estimation of battery capacity is done considering the characteristics of lead-acid battery technology and the electrical pricing mechanism. Based on the results, it is observed that for these typical PV and load profiles, installation a capacity of 2100 Ah lead-acid battery to C6 house will reduce the annual electricity bill by 17.6 % of the bill before installing the battery. Similarly, the annual electricity bill is minimum for a battery capacity of 6000 Ah for Teri university. If this battery capacity (6000 Ah) is added, then the annual electricity bill is reduced by 5500 Indian rupee INR.